Solanum clarum and S. morelliforme as Novel Model Species for Studies of Epiphytism - Jansky, Shelley H.; Roble, Jacob; Spooner, David M. (Frontiers in Plant Science, 2016)
The natural history of epiphytic plant species has been extensively studied. However, little is known about the physiology and genetics of epiphytism. This is due to difficulties associated with growing epiphytic plants and the lack of tools for genomics studies and genetic manipulations. In this study, tubers were generated from 223 accessions of 42 wild potato Solanum species, including the epiphytic species S. morelliforme and its sister species S. clarum. Lyophilized samples were analyzed for 12 minerals using inductively coupled plasma optical emission spectrometry. Mineral levels in tubers of S. morelliforme and S. clarum were among the highest for 10 out of the 12 elements evaluated. These two wild potato relatives are native to southern Mexico and Central America and live as epiphytes or in epiphytic-like conditions. We propose the use of S. morelliforme and S. clarum as model organisms for the study of mineral uptake efficiency. They have a short life cycle, can be propagated vegetatively via tubers or cuttings, and can be easily grown in controlled environments. In addition, genome sequence data are available for potato. Transgenic manipulations and somatic fusions will allow the movement of genes from these epiphytes to cultivated potato.